Posterior urethral valve in children: Using novel biomarkers as an early predictive tool for the onset and progression of chronic kidney disease - Uwaezuoke, Samuel N.; Odimegwu, Chioma L.; Mbanefo, Ngozi R.; Eze, Ikenna C. (Frontiers in Urology, 2022)
This narrative review aims to appraise the current evidence on using biomarkers of obstructive nephropathy to predict the onset and progression of chronic kidney disease (CKD) in infants with posterior urethral valves (PUV). PUV is the most frequently reported congenital anomaly of the kidney and urinary tract (CAKUT) associated with bladder outlet obstruction in male children. It contributes significantly to the CKD burden in childhood. Despite different approaches for its postnatal repair, evidence-based data still suggest a high risk of CKD and end-stage kidney disease (ESKD) later in childhood. In obstructive nephropathy, glomerular and tubulointerstitial lesions contribute to renal impairment. Although it may be difficult to predict these adverse renal outcomes in repaired PUV, detecting and monitoring future CKD appears enhanced using the combination of serum creatinine- or cystatin C-based estimated glomerular filtration rate (eGFR) and albuminuria. Given the drawbacks of these conventional biomarkers, there is a paradigm shift to novel biomarkers as tools for the early identification of glomerular and tubulointerstitial lesions seen in obstructive nephropathy. Most novel biomarkers are yet to be fully applied to routine clinical practice globally. Nevertheless, there is substantial evidence showing that they form part of the emerging diagnostics for obstructive nephropathy. From the reviewed studies, urine transforming growth factor-beta 1 (TGF-β1) is the most prominent biomarker among the novel biomarkers of obstructive nephropathy. However, other novel approaches like the machine learning (ML) model (a form of health-related artificial intelligence) and urodynamic parameters like bladder contractility index hold promise for PUV outcomes prediction (PUVOP). Because of the association of urine TGF-β1 with urine angiotensin level (a biomarker of the renin-angiotensin-aldosterone system [RAAS]), early angiotensin-converting enzyme inhibitor (ACEI) therapy in patients with PUV may potentially retard the progression of CKD and improve renal outcomes. Thus, future research directions should explore the role of ACEI as a pre-emptive treatment for poor renal outcomes in post-valve-ablation patients and conduct longitudinal studies that adequately demonstrate these biomarkers as predictors of these outcomes.